Bibliometric analysis on green hotels: past, present and future trends - Muhammad Ashraf, Fauzi; Han, Heesup; Loureiro, Sandra Maria Correia; Ariza-Montes, Antonio; Wider, Walton (Emerald Publisher, 2024)
Purpose: Service providers and tourism players have introduced the green hotels concept to mitigate detrimental environmental impact. This study aimed to review the literature on green hotels based on bibliometric analysis. Design/methodology/approach: In analyzing the potential and significant subject of the tourism industry and concern on environmental issues, this study evaluates the themes based on the past, present and future trends in green hotels from a bibliographic database retrieved from the Web of Science (WoS). Findings: Several themes were identified from the role of the theory of planned behavior and predictors of consumers' intention to visit green hotels. Practical implications: Implications were discussed mainly related to green hotels contribution towards sustainable tourism and its role in shaping the tourism sector's landscape. Among the practical implications include rewards by the authorities in the form of incentives or tax relief to green hotel operators, which will encourage conventional hotel transformation into green hotels. Furthermore, green hotels will be at the forefront of tourism and hospitality brands, requiring substantial green marketing initiatives. Sooner or later, opting for green hotels while traveling will be the norm among travelers. Originality/value: The green hotels have emerged as a way to tackle the environmental issues related to tourism and hospitality while at the same time, allowing the industry to flourish. This research is one of the scant studies that provide a comprehensive overview about green hotel studies and offer future research agendas.